Development of DS‐5573a: A novel afucosylated mAb directed at B7‐H3 with potent antitumor activity. Issue 5 (26th April 2016) - Nagase‐Zembutsu, Akiko; Hirotani, Kenji; Yamato, Michiko; Yamaguchi, Junko; Takata, Takehiko; Yoshida, Makoto; Fukuchi, Keisuke; Yazawa, Mitsuhiro; Takahashi, Shu; Agatsuma, Toshinori
Abstract : B7‐H3 is highly overexpressed in a variety of human clinical tumors, and its expression is significantly associated with poor outcomes. In our study, we aimed to develop new antitumor mAbs by employing cancer cell immunization, and succeeded in generating a mouse anti‐human B7‐H3 antibody (M30) that shows antitumor activity. M30 was humanized (Hu‐M30), and an afucosylated Hu‐M30 (DS‐5573a) was also generated. To assess the potency of DS‐5573a as a therapeutic mAb, we characterized this mAb and evaluated its antitumor activity in vitro and in vivo . Flow cytometry analysis showed that B7‐H3 proteins were expressed on various types of cancer cell lines broadly, and DS‐5573a binds to IgC1 and IgC2 domains of human B7‐H3. Antibody‐dependent cellular cytotoxicity activity of DS‐5573a was drastically enhanced against medium to high B7‐H3‐expressing cancer cell lines MDA‐MB‐231 and NCI‐H322. DS‐5573a also induced high antibody‐dependent cellular cytotoxicity activity against low B7‐H3‐expressing cancer cell line COLO205, whereas Hu‐M30 induced little activity against it. In addition, DS‐5573a was found to be a novel anti‐B7‐H3 antibody which showed antibody‐dependent cellular phagocytosis activity. Furthermore, DS‐5573a showed dose‐dependent and significant antitumor efficacy (0.03–3 mg/kg) in MDA‐MB‐231‐bearing SCID mice (which have functional natural killer cells and macrophages), but little antitumor efficacy in NOG mice (which lack natural killer cells and have reduced macrophage function). These results suggest that antitumor activity of DS‐5573a is mediated by effector cells, and this mAb could be a promising antitumor therapy for patients with a wide range of B7‐H3‐expressing tumors. Abstract : We developed a novel afucosylated humanized anti‐B7‐H3 monoclonal antibody, DS‐5573a. We found that this mAb has potent antitumor activity against B7‐H3‐expressing cancer cells via natural killer cells and macrophages. Our results suggest that DS‐5573a has potential as a therapeutic mAb to address unmet medical needs in B7‐H3 positive‐cancer patients.